Too Depleted to Turn In: The Relevance of End-of-the-Day Resource Depletion for Reducing Bedtime Procrastination - Kamphorst, Bart A.; Nauts, Sanne; De Ridder, Denise T. D.; Anderson, Joel H. (Frontiers in Psychology, 2018)
Bedtime procrastination is an important predictor of sleep insufficiency in the general population (Kroese et al., 2014a), but little is known about the determinants of this self-undermining behavior. As the phenomenon has been conceptualized in the literature as a form of self-regulation failure (Kroese et al., 2014b), we hypothesized that people's self-regulatory resources in the evening would be predictive of going to bed later than they intended. Specifically, we examined whether the cumulative effect of resisting desires, a measure of self-regulatory resource depletion (Hofmann, Baumeister & Vohs, 2012), relates to bedtime procrastination. Participants (N = 218) reported how many desires they had tried to resist during the previous day and the extent of their bedtime procrastination. Results show that people who attempted to resist more desires were more likely to engage in bedtime procrastination, suggesting that people may be less likely to stick to their intended bedtime after a particularly taxing day. Implications for intervention strategies are discussed.